The Analysis of Main Character in Film the Wolf of Wall Street - Dion, Rikardus; Ida Ayu Putri Gita Ardiantari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The title of this article is to The Analysis of Main Character in Film the Wolf of Wall Street. It mainly aims to find the types of main characters and characterizations of the main characters. This topic was selected through research by using the theory developed by Kenney (1996) which was used to analyze the main character types. This research used descriptive qualitative. The data were collected from the main character's speech in the film and the data source is from the film script. Data were analyzed qualitatively and presented descriptively. Based on the theories adopted in this study, the results of this study indicate that there are several types of characters in this film, one of which is the protagonist. In showing the type of character and the main character, the analysis used is the scene from each film's dialogue. There are two aspects found from the film, namely: physiological aspects, and sociological aspects.